Do serum androgens influence blastocysts ploidy in karyotypically normal women?. (4th July 2019) - Kunicki, Michał; Skowrońska, Patrycja; Pastuszek, Ewa; Jakiel, Grzegorz; Smolarczyk, Roman; Łukaszuk, Krzysztof
ABSTRACT: The aim of the study was to determine if serum testosterone (T) and dehydroepiandrosterone (DHEAS) levels are a factor in determining increased risk for embryonic aneuploidy in karyotypically normal women undergoing in vitro fertilization (IVF) and preimplantation genetic testing screening for aneuploidy (PGT-A). This is a retrospective cohort study of IVF cycles with PGT-A performed during 2015–2016. A total of 256 cycles with 725 embryos were initially considered for inclusion. A total of 208 cycles and 595 embryos determined to be either euploid or aneuploid were included in the analysis. The mean age of women was 37.4 ± 4.4 years. There were 193 (32.44%) euploid, and 338 (56.81%) aneuploid blastocysts. Sixty-four (10.76%) had 'no diagnosis' after PGT-A. The 32 embryos with 'no diagnosis' after first PGT-A were biopsied again and after the second analysis, 7 were found to be euploid and 3 aneuploid. The remaining 32 embryos were not reanalyzed due to the lack of patients' consent for the second biopsy. The relationship between embryo ploidy and levels of serum testosterone and dehydroepiandrosterone sulfate was assessed using ordinal multivariable regression analysis. The model, adjusted for both anti-Mullerian hormone (AMH) and age, showed no association between ploidy status and serum levels of the two hormones. We concluded that the serum levels of testosterone and DHEAS do not influence embryo ploidy in karyotypically normal women undergoing IVF. Abbreviations : T: testosterone; DHEAS: dehydroepiandrosterone; IVF: in vitro fertilization; PGT-A: preimplantation genetic testing screening for aneuploidy; AMH: anti-Mullerian hormone; FSH: follicle-stimulating hormone; LH: luteinizing hormone; E2 : oestradiol; P: progesterone